ХУДОЖЕСТВЕННОЕ НАСЛЕДИЕ АНГЛИИ В ОБУЧЕНИИ АНГЛИЙСКОМУ ЯЗЫКУ - Пирманова, Г.Н. (SCIENCE and SOCIETY, 2020)
The article deals with the pedagogical system of studying by students the literary – artistic heritage of England at extracurricular classes. The author characterizes the content of components of the pedagogical system and stages of studying the literary-artistic creation of the prominent workers of culture of England directed to the increasing students’ interest to the English language.